Mobile Drip Irrigation Evaluation in Corn - I. Kisekka; T. Oker; G. Nguyen; J. Aguilar; D. Rogers (Kansas Agricultural Experiment Station Research Reports, 2016)
Mobile Drip Irrigation (MDI) involves attaching driplines to center pivot drops. MDI has potential to eliminate water losses due to spray droplet evaporation, water evaporation from the canopy, and wind drift. MDI also may reduce soil water evaporation due to limited surface wetting. A study was conducted with the following objectives: 1) compare soil water evaporation under MDI and in-canopy spray nozzles; 2) evaluate soil water redistribution under MDI at 60 inch dripline lateral spacing; 3) compare corn grain yield, water productivity, and irrigation water use efficiency; and 4) compare end-of-season profile soil water under MDI and in-canopy spray at two well capacities 300 and 600 gpm. The experiment was conducted at the Kansas State University Southwest Research-Extension Center near Garden City, Kansas. The experimental design was randomized complete block with four replications, and two treatments MDI and in-canopy spray nozzles. Soil water evaporation was measured using four-inch mini-lysimeters placed between corn rows. The effect of a 60-inch lateral spacing on soil water redistribution was evaluated using soil water measurements made using neutron attenuation to a depth of 8 feet. Preliminary results indicate soil water evaporation was lower under MDI compared to in-canopy spray nozzles, by 35% on average. Soil water redistribution was adequate for dripline spacing of 60 inches in silt loam soils of southwest Kansas. At 600 gpm well capacity, corn yields were 247 and 255 bu/a for MDI and in-canopy spray nozzles, respectively. At 300 gpm well capacity, yields were 243 and 220 bu/a for MDI and in-canopy spray nozzles, respectively. However, the differences were not significant (p>0.05) between the irrigation application technologies in 2015. The effect of application method on water productivity and irrigation water use efficiency was also not significant. The lack of significant differences could be attributed to the above normal rainfall received during the 2015 growing season (18.3 inches from May to October). Normal mean annual rainfall for the study area is 18 inches. The effect of application method on end-of-season soil water was statistically significant under low well capacity (300 gpm) with Mobile Drip Irrigation having more soil water compared to in-canopy spray nozzles in the 8 foot profile at harvest. It is worth noting that plots under MDI did not have deep wheel tracks associated with sprinkler nozzles.
Keywords: mobile drip irrigation; soil water evaporation; in-canopy; corn; spray droplet evaporation; irrigation management; soil water redistribution; crop water use; end of season soil water